Etika Lingkungan dalam Tradisi Cingcowong pada Masyarakat Luragung Landeuh, Kecamatan Luragung - Wina Waniatri; Ilham Adhya; Nina Herlina; Nurdin Nurdin; Anoydya Firsha Az-zikra; Fadly Alamsyah (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Environmental ethics assumes that nature has human values ​​that must be respected. Various forms of embedding can be done, such as the traditional Cingcowong ceremony. The Cingcowong tradition is a traditional ritual originating from the agricultural community of Luragung Landeuh Village, Kuningan Regency. This tradition is a form of collective community activity that is based on belief in supernatural spirits who are believed to have the power to bring rain to overcome drought, especially on agricultural land caused by prolonged drought. Cingcowong reflects the close relationship between culture, nature, and spiritual practices in certain societies. In the context of environmental ethics, this tradition can be seen as a form of local wisdom that shows respect for nature, an understanding of the importance of ecosystem balance, and an awareness of human dependence on weather conditions. Therefore, this tradition can be considered as a concrete manifestation of environmental ethics that encourages humans to appreciate nature more and understand the interaction between spiritual, cultural, and environmental factors.